(untitled) (National Administration Journal, 2021)
This study has focused on the GoFundMe platform, which is considered to have the highest volume of campaigns related to COVID-19. GoFundMe is a platform that falls within the donation crowdfunding modality. The main objective of this paper consists of the analysis of the crowdfunding campaigns related to COVID-19, which have been collected manually from the GoFundMe platform, in order to carry out a description of the characteristics of a sample random of 118 projects. Through the use of different techniques of descriptive statistical analysis, a set of quantitative variables are analyzed, such as the type of project, amount collected, target amount, and statistics on fundraising related to the number of donors, times shared and followers, among others.